2014
DOI: 10.1371/journal.pone.0096628
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk in Mechanomyographic Signals from the Forearm Muscles during Sub-Maximal to Maximal Isometric Grip Force

Abstract: PurposeThis study aimed: i) to examine the relationship between the magnitude of cross-talk in mechanomyographic (MMG) signals generated by the extensor digitorum (ED), extensor carpi ulnaris (ECU), and flexor carpi ulnaris (FCU) muscles with the sub-maximal to maximal isometric grip force, and with the anthropometric parameters of the forearm, and ii) to quantify the distribution of the cross-talk in the MMG signal to determine if it appears due to the signal component of intramuscular pressure waves produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 19 publications
4
13
2
Order By: Relevance
“…33 In addition, the length and circumference of the forearm also influences the level of crosstalk in the MMG signal. 40 …”
Section: Discussionmentioning
confidence: 99%
“…33 In addition, the length and circumference of the forearm also influences the level of crosstalk in the MMG signal. 40 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, for an improved signal integrity, the standard practice include the use of double sided adhesive tape to fix the MMG's sensor to the skin in order to ensure a constant pressure. Isolation of irrelevant muscles through an experimental setup on standard testing devices such as custom made or commercially available dynamometers has been suggested to limit the yet unavoidable effects of cross-talk [ 43 ].…”
Section: Technical Characteristics Of Mmg Sensors Selection Criteriamentioning
confidence: 99%
“…The data stored on a personal computer were first digitally bandpass filtered (fourth order Butterworth) at 5–100 Hz to obtain the MMG signals, and the MMG signals from the 2 seconds corresponding to the middle 33% of each 6 second isometric contraction were then extracted to remove the effect of signal transition, as recommended by 38 . The dominant power in MMG frequency spectrum was found outside the tremor range (5–12 Hz) 25 . The power density spectra of MMG signal from the three muscles of a subject performing forearm flexion, pronation and supination tasks are shown in Fig.…”
Section: Methodsmentioning
confidence: 96%
“…The authors found a weak negative correlation between these parameters measured from the biceps brachii (BB) using an accelerometer during isometric contractions. The correlation between the forearm circumference and CT in MMG signals was quantified by 25 during an isometric grip force task and was found to be weakly positive. Similarly, the effect of variations in the forearm circumference on CT in sEMG signals was also discussed by 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation